2008
DOI: 10.1016/j.neulet.2008.05.117
|View full text |Cite
|
Sign up to set email alerts
|

Impact of apoE deficiency during synaptic remodeling in the mouse olfactory bulb

Abstract: In this study we examined the role of apoE on the rate of synaptic recovery in the olfactory bulb (OB) following olfactory epithelium (OE) lesioning in mice. We used both immunoblotting and immunohistochemical techniques to compare the density of OB synaptophysin (Syn, a synaptic marker) in apoE-gene deficient/knockout (KO) mice and wild-type (WT) mice following OE lesion. We found that the whole bulb concentrations of Syn, measured by immunoblotting, declined sharply following injury in both WT and KO mice du… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 27 publications
1
10
0
Order By: Relevance
“…In mice that are genetically deficient of APOE , the rate of olfactory nerve regeneration in the OE is significantly delayed, along with multiple measures of olfactory function (6668). Although the synaptic integrity of the OB is also compromised in the APOE deficient mice (69), it is not yet known whether its regenerative capacity is also decreased or delayed. Interestingly, estrogen treatment has been shown to stimulate the regeneration of OE and synaptogenesis of OB in an APOE -dependent manner (70).…”
Section: Olfactory System In Aging and Admentioning
confidence: 99%
“…In mice that are genetically deficient of APOE , the rate of olfactory nerve regeneration in the OE is significantly delayed, along with multiple measures of olfactory function (6668). Although the synaptic integrity of the OB is also compromised in the APOE deficient mice (69), it is not yet known whether its regenerative capacity is also decreased or delayed. Interestingly, estrogen treatment has been shown to stimulate the regeneration of OE and synaptogenesis of OB in an APOE -dependent manner (70).…”
Section: Olfactory System In Aging and Admentioning
confidence: 99%
“…Another factor that may mediate estradiol-induced neuroglial plasticity is apolipoprotein E (ApoE) (Struble et al, 2007), which levels have been shown to depend on gonadal steroid levels in vivo and in vitro (Stone et al, 1997;Struble et al, 2007). Although the precise mechanisms of ApoE in neuro-glial plasticity are still unknown, this molecule seems to be crucial for that function (Blain et al, 2006;Nwosu et al, 2008;White et al, 2001) and it is involved in the effects of estradiol on axonal growth in vitro (Nathan et al, 2004).…”
Section: Astrocytes As Cellular Targets Of Gonadalmentioning
confidence: 99%
“…One possible explanation for this difference is that cell genesis rates in KO and WT are comparable but, as we have shown axonal growth and synaptogenesis following a lesion of the OE are delayed in KO mice (Nathan et al, 2005; Nwosu et al, 2008). Hence, increased OMP cell density in WT OE, regardless of estradiol replacement indicates that apoE facilitates maturation of OSN to phenotypically adult cells.…”
Section: Discussionmentioning
confidence: 82%
“…Overall, estradiol was associated with increased Syn but the baseline level and magnitude of increase was suppressed by the absence of apoE. A decrease in Syn staining has been shown in the hippocampus, neocortex, and OB of apoE KO mice (Masliah et al, 1995; Nwosu et al, 2008). Our data parallel these previous studies and present a possible mechanism to explain this.…”
Section: Discussionmentioning
confidence: 91%